Bioremediation Potential of Mushrooms - Jain, Sudhir Kumar; Pandey, Akhilesh Kumar (International Journal of Scientific Research in Biological Sciences, 2021)
Potential of Mushroom to work as Bio-remediating agent has made a significant remark in the field of Environment Management. Ability of mushrooms to grow on agro-industrial waste has made researchers to ponder over the new and better possibilities to clean the environment. There are certain things which are yet to be explored like oil is a mixture of a number of toxic derivatives. Can mushrooms eradicate or detoxify all of them? Secondly, Can the edible species of mushroom involved in bioremediation, be declared safe to use? Restoration of polluted land can be used to grow food crops or not? So, there is a lot to explore yet. Although, this practice has a lot of future prospects, carrying forward the economic concept of Mushroom Cultivation Technique & its role in Bioremediation.